2022
DOI: 10.34117/bjdv8n1-456
|View full text |Cite
|
Sign up to set email alerts
|

O hidrocondicionamento pode ser uma estratégia para aumentar o desempenho das sementes de calêndula? / Can hydro-conditioning be a strategy to increase the performance of marigold seeds?

Abstract: A Calêndula (Calendula officinalis L.) é uma planta hortícola utilizada como ornamental, cosmética e também por suas propriedades medicinais, que é reconhecida por importantes órgãos governamentais, como o Ministério da Saúde do Brasil. As sementes de calêndula têm germinação baixa e desigual, sendo necessário estudar métodos de pré-germinação para aumentar a propagação e estabelecimento da cultura em larga escala. No presente estudo, objetivou-se avaliar a influência do hidrocondicionamento em diferentes perí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…We suggested that this response is associated with possible damage caused by hydropriming due to the low water content in the Table 1 -Results of the analysis of variance of the effect of hydropriming, substrates and the interaction on the characteristics evaluated in Calendula officinalis L. seedlings. seeds (6.1%), that is, exposure to water for 24 hours may have been too long, and also due to the fact that the seeds of this species have low water content (LOPES et al, 2022), which caused release of electrolytes and damage to membranes (LEMMENS et al, 2019). Similarly, Dalbergia nigra (Vell.)…”
Section: Resultsmentioning
confidence: 99%
“…We suggested that this response is associated with possible damage caused by hydropriming due to the low water content in the Table 1 -Results of the analysis of variance of the effect of hydropriming, substrates and the interaction on the characteristics evaluated in Calendula officinalis L. seedlings. seeds (6.1%), that is, exposure to water for 24 hours may have been too long, and also due to the fact that the seeds of this species have low water content (LOPES et al, 2022), which caused release of electrolytes and damage to membranes (LEMMENS et al, 2019). Similarly, Dalbergia nigra (Vell.)…”
Section: Resultsmentioning
confidence: 99%
“…Sabe-se que o teor de água da semente influencia a taxa e velocidade de absorção de água (Lopes et al, 2022). Embora a literatura relate muitos benefícios da hidratação descontínua de sementes (Lima et al, 2018b;Freitas et al, 2021;Nascimento et al, 2021;Jain et al, 2022), algumas espécies como Myracrodruon urundeuva,…”
Section: Resultsunclassified
“…apresentaram danos nos parâmetros germinativos conforme o aumento do número de ciclos de HD (Hora;Meiado, 2016;Lima et al, 2018ª;Lopes et al, 2022). Assim, é essencial identificar os efeitos dessa técnica para identificar o tempo e o número ideal de ciclos (Santos Júnior et al, 2021).…”
Section: Resultsunclassified